THE EFFECT OF HEALTH EDUCATION ON THE KNOWLEDGE AND BEHAVIOR OF PREGNANT WOMEN ABOUT COVID-19 IN RAMBAH TENGAH HILIR VILLAGE, RAMBAH DISTRICT, ROKAN HULU REGENCY - Romy Wahyuny; Andria, Andria; Ermiza, Ermiza (Journal of Islam and Science, 2022)
Complications that often occur in pregnant women infected with the COVID-19 virus include respiratory failure, heart problems, impaired blood clotting, kidney disorders and secondary infections by other microorganisms. While the effect on the baby is premature delivery and fetal death in the womb. The purpose of this study was to determine the effect of health education on knowledge and behavior of pregnant women about the COVID-19 disease in Rambah Tengah Hilir Village, Rambah District, Rokan Hulu Regency. This type of research is a quantitative study using a pre-experimental one group pre-post test design. The number of samples is 64 people who are determined by the total sampling technique. The statistical test used is the paired t test. The results showed that the average knowledge of respondents before being given health education about COVID-19 was 2.10 and after being given health education it was 1.04. As for the behavior of respondents before being given health education the average was 1.46 and after being given health education it was 1.06. Based on the results of statistical tests, there is an effect of health education on mother's knowledge and behavior about COVID-19 with statistical test results obtained p-values are 0.001 and 0.0004 (p<0.05). It is hoped that pregnant women will continue to apply the 5 M (wearing a mask, maintaining distance, washing hands, avoiding crowds and reducing mobility) so that the chain of spreading COVID-19 is broken.